Apophasis, contemplation, and the kenotic moment in Anglo-Saxon literature - Flight, T (2016)
This thesis reveals the considerable influence of contemplation (sometimes referred to as mysticism) on Anglo-Saxon literature, manifested through the arrangement of narratives according to the theological concepts of apophasis and kenosis. This is demonstrated through a lengthy contextual discussion of the place of contemplation in Anglo-Saxon spirituality, and close analysis of four poems and a prose text. Although English mysticism is commonly thought to start in the High Middle Ages, this thesis will suggest that this terminus post quem should instead be resituated to the Anglo-Saxon period. The first chapter seeks to reveal the centrality of contemplation to Anglo-Saxon spirituality through analysing a range of diverse material, to evidence the monastic reader borne from this culture capable of reading and composing the texts that make up the rest of the thesis in the manner suggested. The thesis places chronologically diverse Anglo-Saxon texts in a contemplative context, with close reference to theology, phenomenology, and narrative structure, to suggest that our interpretation of them should be revised to apprehend the contemplative scheme that they advocate: to cleanse the reader of sin through inspiring penitence and kenosis (humility and emptying of one’s will) and direct the mind intellectually beyond the words, images and knowledge of the terrestrial sphere (apophasis), so as to prepare them for the potential coming of God’s grace in the form of a vision. This reading is supported by the close taxonomical resemblance of each text’s narrative structure. The thesis thus suggests that contemplation was central to Anglo-Saxon spirituality, producing an elite contemplative audience for whom certain texts were designed as preparative apparatus.